Adsorption of propane,propylene and isobutane on a metal-organic framework : molecular simulation and experiment - Nabil Lamia (2009)
The separation of propane/propylene mixtures is the most energy-intensive operation practiced in thepetrochemical industry. Adsorptive processes are currently viewed as a promising alternative to cryogenicdistillation for the separation of these mixtures. In this paper, we explore the possibility of using a newmetalorganic framework material, CuBTC, in adsorptive separation processes, particularly in a simulatedmoving bed (SMB) context using isobutane as a potential desorbent. A gravimetric method has been usedto measure the adsorption equilibrium isotherms of propylene, propane and isobutane onto a commercialCuBTC powder over a temperature range from 323 to 423 K and pressures up to 100 kPa. These werecomplemented by a detailed experimental characterization of the structure of CuBTC using XRD andSEM techniques. Comparison of experimental isotherms with grand canonical Monte Carlo simulations inCuBTC showed that propane adsorption occurs preferentially in small octahedral pockets, while isobutaneis excluded from these pockets due to its bulky structure. Propylene was seen to interact stronglywith unsaturated metal sites, due to specific -Cu bonds. These interactions significantly enhance theaffinity of this MOF for unsaturated hydrocarbons. Furthermore, in a range of temperatures and pressures,the affinity of CuBTC for isobutane is intermediate to that of propane and propylene. Our resultssuggest that CuBTCisobutane is a very promising adsorbentdesorbent pair for use in SMB processes forpropane/propylene separations.